2002
DOI: 10.1063/1.1450548
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of iron carbide, FeC

Abstract: Employing multireference variational methods ͑MRCI͒, we have constructed full potential-energy curves for the ground state (X 3 ⌬) and forty excited states of the diatomic carbide, FeC. For all states we report potential-energy curves, bond lengths, dissociation energies, dipole moments, and certain spectroscopic constants, trying at the same time to get some insight on the bonding mechanisms with the help of Mulliken populations and valence-bond-Lewis diagrams. For the X 3 ⌬ state at the MRCI level of theory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 31 publications
(37 reference statements)
11
78
1
1
Order By: Relevance
“…This distance is similar to that reported in Fe and Ni carbides, surfaces and the C interaction as an impurity with line defects. The charge transference to Ni and C and the DOS plots agrees with theoretical results in the literature [6,34,[56][57][58][59].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This distance is similar to that reported in Fe and Ni carbides, surfaces and the C interaction as an impurity with line defects. The charge transference to Ni and C and the DOS plots agrees with theoretical results in the literature [6,34,[56][57][58][59].…”
Section: Discussionsupporting
confidence: 89%
“…After optimization, the Fe-C and Ni-C present almost an equivalent distance of 1.80 Å. In a recent paper, Tzelei and Mauridis [56] report that in gas-phase diatomic species Fe-C and Ni-C present bond distances from 1.5 Å to 2.0 Å. Niu et al [57] reported a Fe-C distance near the dislocation core of 1.84 Å using ab-initio calculations. Wu et al [58] report found a distance of 1.80 Å when C is located in a Fe grain boundary.…”
Section: Absorptionmentioning
confidence: 97%
“…In a recent work, Tzeli and Mavridis reported that in gas phase diatomic species Fe-C and Ni-C present bond distances from 1.5 Å to 2.0 Å [51]. The Fe-C distance is similar to that reported by Niu et al near a dislocation core in α-Fe of 1.84 Å [52] and by Wu et al on the (111) surface (1.80 Å) [53].…”
Section: Original Papersupporting
confidence: 61%
“…Lambda-doubling is caused by perturbations by nearby excited electronic states, in particular 3 P, 1 P, 1 S, and 3 S terms for 3 D ground states. As suggested by ab initio calculations (Shim & Gingerich 1999;Tzeli & Mavridis 2002), such states exist in the FeC manifold, but with the exception of a 3 S Ϫ state, lie quite high in energy (i.e., 115,000 cm Ϫ1 ). Because the magnitude of the lambda-doubling interaction is inversely proportional to the energy differences between the ground and perturbing excited states, the effect of these highlying levels is mitigated.…”
Section: Discussionmentioning
confidence: 96%